Attenuation of MODS-related and ARDS-related mortality makes infectious complications a remaining challenge in the severely injured. Issue 1 (4th February 2020) - van Wessem, Karlijn J.P.; Hietbrink, Falco; Leenen, Luke P.H.
Abstract : Introduction: The recent decrease in multiple organ dysfunction syndrome (MODS)-associated and adult respiratory distress syndrome (ARDS)-associated mortality could be considered a success of improvements in trauma care. However, the incidence of infections remains high in patients with polytrauma, with high morbidity and hospital resources usage. Infectious complications might be a residual effect of the decrease in MODS-related/ARDS-related mortality. This study investigated the current incidence of infectious complications in polytrauma. Methods: A 5.5-year prospective population-based cohort study included consecutive severely injured patients (age >15) admitted to a (Level-1) trauma center intensive care unit (ICU) who survived >48 hours. Demographics, physiologic and resuscitation parameters, multiple organ failure and ARDS scores, and infectious complications (pneumonia, fracture-related infection, meningitis, infections related to blood, wound, and urinary tract) were prospectively collected. Data are presented as median (IQR), p<0.05 was considered significant. Results: 297 patients (216 (73%) men) were included with median age of 46 (27–60) years, median Injury Severity Score was 29 (22–35), 96% sustained blunt injuries. 44 patients (15%) died. One patient (2%) died of MODS and 1 died of ARDS. 134 patients (45%) developed 201 infectious complications. Pneumonia was the most common complication (50%). There was no difference in physiologic parameters on arrival in emergency department and ICU between patients with and without infectious complications. Patients who later developed infections underwent more often a laparotomy (32% vs 18%, p=0.009), had more often pelvic fractures (38% vs 25%, p=0.02), and received more blood products <8 hours. They had more often MODS (25% vs 13%, p=0.005), stayed longer on the ventilator (10 (5–15) vs 5 (2–8) days, p<0.001), longer in ICU (11 (6–17) vs 6 (3–10) days, p<0.001), and in hospital (30 (20–44) vs 16 (10–24) days, p<0.001). There was however no difference in mortality (12% vs 17%, p=0.41) between both groups. Conclusion: 45% of patients developed infectious complications. These patients had similar mortality rates, but used more hospital resources. With low MODS-related and ARDS-related mortality, infections might be a residual effect, and are one of the remaining challenges in the treatment of patients with polytrauma. Level of evidence: Level 3. Study type: Population-based cohort study.